Feminism in Literature: A Study of Emecheta’s the Joys of Motherhood and Nwapa’s Efuru - Eneremadu Queen Esther Chioma; Eze Mabel Nkechinyere (International Journal of Sustainable Applied Sciences, 2023)
This Paper is concerned with the motives, concepts and ideas expressed by African female writers in their works. They speak with one voice; they fight for the recognition and emancipation of women in male dominated societies. They use their works to air their views. They aim for the equality of all sexes. This study shows the aims of female writers in literature which seeks to bring an end to the oppression and subordination of women by men. It is worthy to note that these African female writers used in this study do not revolt against men but against certain laws that have denied them their inalienable rights. This study has investigated the aims of female writers in literature using two novels: Efuru by Flora Nwapa and The Joys of motherhoodby Buch Emecheta. These two authors have artistically used their novels to expose the ugly experiences of women in a male dominated society. This work however discovers in dismay that in most cases, women maltreat their fellow women in the name of tradition. The significance of this work derives in the fact that it joins the voices of previous researchers to encourage women, both readers and writers to rise up and be liberated from the long craws of male chauvinism. The researcher therefore believes that these complementary efforts shell help in proving suitable society where women are to be recognized.